Influence of organizational culture, supervision and environmental work towards discipline of Cicau village employees - Rahmat Hidayat; Dadang Heri Kusumah (STIE Binaniaga, 2019)
Each organization is required to be able to optimize human resources and human resources who are able to work hard and have high productivity. Achieving high productivity is not an easy thing to do. An important factor for achieving high productivity is the implementation of work discipline from its employees. In order for the company's operational activities to run well, supervision is needed. The purpose of supervision is for employees to be careful in their work. Supervision is very important, because with the supervision, the employee is serious in working. In addition, the work environment plays an important role in humans who play a role in achieving success in human endeavor or work. The main basis for implementing the work environment is knowledge and attention to human behavior as a determining factor for organizational success. This study aims to determine the effect of organizational culture, supervision and work environment on village employee work discipline. This type of research is quantitative. For data collection includes observations, questionnaires, and literature studies. The analytical methods used are validity test, reliability test, classic assumption test, multiple linear analysis and hypothesis testing. Keywords: Organizational culture, Supervision, Work environment, and work discipline.